Bacterial ApbC can bind and effectively transfer iron-sulfur clusters - Boyd, Jeffrey M. (2008)
The metabolism of iron-sulfur ([Fe-S]) clusters requires a complex set of machinery that is still being defined. Mutants of Salmonella enterica lacking apbC have nutritional and biochemical properties indicative of defects in [Fe-S] cluster metabolism. ApbC is a 40.8 kDa homodimeric ATPase and as purified contains little iron and no acid-labile sulfide. An [Fe-S] cluster was reconstituted on ApbC, generating a protein that bound two moles of Fe and two moles of S(2-) per ApbC monomer and had a UV-visible absorption spectrum similar to known [4Fe-4S] cluster proteins. Holo-ApbC could rapidly and effectively activate Saccharomyces cerevisiae apoisopropylmalate isolomerase (Leu1) in vitro, a process known to require transfer of a [4Fe-4S] cluster. Maximum activation was achieved with two moles of ApbC per one mole of apo-Leu1. This report describes the first biochemical activity of ApbC in the context of [Fe-S] cluster metabolism. The data herein support a model in which ApbC coordinates an [4Fe-4S] cluster across its dimer interface and can transfer this cluster to an apo-protein acting as an [Fe-S] cluster scaffold protein, a function recently deduced for its eukaryotic homologues.